PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KETERAMPILAN MEMECAHKAN MASALAH AUTENTIK SISWA PADA MATERI POKOK HUKUM NEWTON KELAS X SEMESTER I SMA NEGERI 1 SEI SUKA T.A 2016/2017 - Berutu, Sari Malum; Harahap, Mara Bangun (JURNAL IKATAN ALUMNI FISIKA UNIVERSITAS NEGERI MEDAN, 2018)
This study aims to determine the effect of learning model Effects of Problem Based Learning Model Against Authentic Problem Solving Skills Students On Main Material Newtons Law Class X Semester Sma Negeri 1 Sei Suka T.A 2016/2017. This research is a quasi-experimental. The population in the study were all students of class X Semester SMA N 1 Sei Suka consisting of 5 classes. Sampling was done by cluster random sampling by taking two classes of fifth grade were randomly ie class X MIA 2 as an experimental class of 40 persons and class X MIA 3 as the control classes of 40 people. The instrument used to determine student learning outcomes is the achievement test in the form of essay test with the number of 10 questions. Based on the analysis of data obtained pretest and posttest results of both classes of normally distributed and come from a homogenous group. Postes results obtained an average grade experiment using the model of Problem Based Learning at 83.65 with a standard deviation of 7.98 and in the control group gained an average post-test score of students at 70.95 with a standard deviation of 8.62. Postes data normality test results for an experimental class obtained Lhitung <Ltabel 0.1246 <0.1401, while for grade control Lhitung <Ltabel 0.0438 <0.1401 thus concluded that the data postes of both classes of normally distributed.